Pengembangan LKPD Berbasis Problem-Based Learning (PBL) dalam Pengolahan Limbah Blotong Tebu pada Submateri Pencemaran Lingkungan di SMP/MTs - Pingky Yogi Septiani; Laily Yunita Susanti (Jurnal Kajian Pendidikan IPA, 2026)
This study aims to determine the validity, practicality, and effectiveness of Problem-Based Learning (PBL)-based Student Worksheets (LKPD) for processing sugarcane bagasse waste within the sub-topic of environmental pollution at junior high schools (SMP/MTs). This study employed the Research and Development (R&D) method using the 4D development model, which includes the Define, Design, Develop, and Disseminate stages. The study was conducted at MTs Hasanuddin Semboro with 26 participants. Data collection techniques included student needs analysis, interviews, validation questionnaires, practicality questionnaires, and learning outcome tests in the form of pre-tests and post-tests. The results showed that the PBL-based worksheets achieved a validity percentage of 91.625%, categorized as highly valid; a practicality percentage of 85.15%, categorized as highly practical; and an N-Gain value of 0.62, categorized as moderate. Based on these results, the PBL-based worksheets on sugarcane bagasse waste processing are deemed valid, practical, and effective, making them suitable for use in science instruction on environmental pollution in junior high schools (SMP) and Islamic junior high schools (MTs).Keywords: Teaching materials, PBL-based student worksheets, sugarcane blotong waste, environmental pollution sub-material